Design And Construction Of Automatic Safety System Potato Stick Cutting Machine - Aidil Zamri; Yuliarman, Yuliarman; Zulhendri, Zulhendri; Menhendri, Menhendri; Rosadi, Nabilla Azzah (Universitas Negeri Padang, 2024)
This research aims to develop a potato stick cutting machine with an automatic safety system, which is a crucial step in supporting the sustainable growth and development of the French fries industry. The methodology used includes a literature review, needs identification, conceptual design, machine fabrication, and testing. In determining the allowable tensile stress of the material, the value used is 120 N/mm², while for the torsional stress and bending stress of the shaft, the values are 96 N/mm² and 120 N/mm² respectively. Planning the pulley involves using a pulley with a diameter of 76.2 mm, while belt selection involves using a type A V-belt with a length of 48.50 inches. The shaft axis distance is also determined with a correction of 503 mm. Test results show that the machine is capable of achieving a production capacity of 84 kg/hour when equipped with an automatic safety system. This machine also facilitates further processing and opens opportunities for small and medium-sized enterprises (SMEs) to utilize it in potato stick production. This research contributes significantly to the development of the potato processing industry by providing a reliable and efficient solution for potato stick production. Thus, this study is crucial for advancing the overall French fries industry sector.